H3K4me3 - dependent epigenetic memory regulates transcriptional reactivation in the oocyte - Navarro-Costa, P. (2015)
Study question: How does the oocyte regulate its transcriptional activity in light of its prolonged meiotic arrest? Summary answer: A histone methylation-mediated epigenetic memory programed by the demethylase KDM5 is required for the correct temporal reactivation of the oocyte's transcriptional activity. What is known already: During oogenesis oocytes transit from stages of transcriptional activity to those of transcriptional quiescence, and such transitions are believed to be essential for proper gamete formation. Although the temporal regulation of these transitions has been well documented across diverse organisms, the molecular mechanisms underlying these processes remain largely unknown.